Does Palapa Ring Project Infrastructure Bridging Connectivity and Economic Activity? - Realita Eschachasthi; Taly Purwa; Diyang Gita Cendekia (Proceedings of The International Conference on Data Science and Official Statistics, 2021)
This study examines the impact of existence of the Indonesian Palapa Ring Project (PRP) infrastructure on connectivity and economic activities in 46 districts in the West, Central, and East package of PRP in 2015-2020. Connectivity is an internet activity that measured by using percentage of internet use and economic activity is measured by using Gross Regional Domestic Product (GRDP). The fixed effect staggered difference-in-difference is utilized to analyze the panel data obtained from Badan Pusat Statistik (BPS)-Statistics Indonesia. An examination of parallel trend assumptions, robustness check, and heterogeneity analysis are also presented. The results show that PRP infrastructure has a positive and significant impact on connectivity; yet has no significant effect on economic activity. In response to the findings, the policy should be designed by intensifying coverage and quality of the internet; proliferating Information Communication Technology (ICT) facilities in rural areas; and expanding education and digital literacy programs.